Temoporfin-in-Cyclodextrin-in-Liposome—A New Approach for Anticancer Drug Delivery: The Optimization of Composition - Ilya Yakavets; Henri-Pierre Lassalle; Dietrich Scheglmann; Arno Wiehe; Vladimir Zorin; Lina Bezdetnaya (Nanomaterials, 2018)
The main goal of this study was to use hybrid delivery system for effective transportation of temoporfin (meta-tetrakis(3-hydroxyphenyl)chlorin, mTHPC) to target tissue. We suggested to couple two independent delivery systems (liposomes and inclusion complexes) to achieve drug-in-cyclodextrin-in-liposome (DCL) nanoconstructs. We further optimized the composition of DCLs, aiming to alter in a more favorable way a distribution of temoporfin in tumor tissue. We have prepared DCLs with different compositions varying the concentration of mTHPC and the type of β-cyclodextrin (β-CD) derivatives (Hydroxypropyl-, Methyl- and Trimethyl-β-CD). DCLs were prepared by thin-hydration technique and mTHPC/β-CD complexes were added at hydration step. The size was about 135 nm with the surface charge of (−38 mV). We have demonstrated that DCLs are stable and almost all mTHPC is bound to β-CDs in the inner aqueous liposome core. Among all tested DCLs, trimethyl-β-CD-based DCL demonstrated a homogenous accumulation of mTHPC across tumor spheroid volume, thus supposing optimal mTHPC distribution.